People's wellbeing, civic capital and sustainable practices: Evidence from the European Values Study survey - Ciziceno, Marco (Frontiers in Sociology, 2023)
The climate change issue is showing an unprecedented level of awareness in the political realm and public opinion. The transformation of occasional sustainable practices into stable, responsible behaviors is crucial to mitigate environmental concerns. However, what makes people environmentally aware is an unsolved question, and research on this direction is in evolution. This paper contributes to the existing literature on factors that promote environmentally responsible behaviors. The study tests the novel hypothesis that people’s well-being predisposes individuals toward environmentalism. The mechanism of social and civic capital may underlie this association, considering that people higher in well-being show empathy, solidarity, and greater civic engagement. This hypothesis is examined in the context of the European Union using micro-data from the European Values Study – EVS (wave 2017–2022). Results support the idea that acting environmentally is an expression of civicness and that people in a positive mood (more satisfied or happy) often report a higher level of civic capital, as they share beliefs and values that encourage the pursuit of socially valuable activities.